Naphthylene−γ: proposição teórica de sistemas 1D e 2D formados por blocos fenil e naftil interligados por anéis quadrangulares - BESERRA, David Joseph Pereira (2022)
Since synthesizing graphene in 2004, the search for modification in its properties, specialty the electronic one, has motivated the study of carbon allotropes with different symmetries that disrupt the graphene’s traditional honeycomb lattice. In addition to the geometric modifications, an efficient approach to tune the electronic properties of carbon-based materials is, since heteroatom insertion, to a complete system composed of another chemical species, like boron nitride, or simply BN. From a fundamental point of view, boron and nitrogen have deficiency and excess of one valence electron relative to carbon, and they have similar atomic radii. Here, a new carbon allotrope is proposed. It is named the naphthylene-γ, which is theoretically constructed by combining phenyl-like (P) and naphthyl-like (N) blocks joined by 4-membered links, resulting in a system with large 10- and 12-ring pores. Furthermore, the naphthylene-γ is suitable to be cast into a boron- nitride configuration since it is a bipartite structure featuring only even-membered rings. It turns out BN configurations of naphthylene-γ can potentially result in systems suitable to be embedded into nanoelectronics applications since they are expected to exhibit robust band gaps. With this motivation, several hybrid systems were hypothetically proposed by replacing part of naphthylene-γ’s C atoms for BN sectors with different concentrations. It was utilized first-principles calculations based on Density Functional Theory (DFT), implemented on the SIESTA code. The naphthylene-γ has a semiconductor behavior, and theory predicts that this property is shared by its nanoribbon counterparts. The computational analysis also indicates the electronic structure of these systems is dictated by quasi-1D states due to the interplay between the system’s geometry (e.g., chirality and edge structure) and its electronic properties. The energy gap for the hybrid γ systems does not vary monotonically with increasing BN concentration. In fact, strategical choices for the sites undergoing C-to-BN substitution result in specific modifications in the electronic signature of the systems. It was also investigated full-BN naphthylene-γ sheets, which show band gaps significantly different from those of hexagonal-BN. It further investigated nanoribbons based on these BN sheets, showing that they closely follow the properties of their parent 2D structure as they feature frontier states internally located over the ribbon structures.